Engenho utópico e amizades proibidas: produção de masculinidades em romances de José Lins do Rego (1931- 1933) - Rocha, Samuel Rodrigues da (2016)
This study fits into the research line of History of Education and aims to understand how masculinities were produced in literary discourse of José Lins do Rego, among the years 1931 to 1933. This time frame takes for reference the years of publication of the works of the author chosen: Menino de engenho and Doidinho. We made the methodological choice of sources readback and working with convergent and divergent discourses, also using the speeches Semanario Illustrado Novidade, that circulated in 1931, the numbers of Revista do Ensino da Paraíba, which circulated in 1932 and 1933 and the passive correspondence of the author with Gilberto Freyre in the time frame period. By working with literature as the main source, we seek theoretical support in Roger Chartier, using his theories about representation and taking masculinities from studies on gender, mainly based in Joan Scott, who stresses the relational character of this category, and Albuquerque Junior, who has dedicated himself to studying masculinities, especially in the context of the Northeast of Brazil, seeking to hold a dialogue among the theories on gender, masculinity and discussions on power, author, space and discourse, as a producer of subjectivities, in Michel Foucault. From these theoretical perspective, we understand that the studied speeches show a clash between renovating and traditionalist forces in the years 1931, 1932 and 1933, which made José Lins do Rego producer in the studied novels, models of masculinity linked to spatiality and to horizontal forms of sociability. Keywords: